Exploring Cosmopolitanity and Connectivity in The Polycentric German Urban System. (5th March 2015) - Growe, Anna; Volgmann, Kati
Abstract: This paper investigates the theoretical concept that a city is always influenced by the relations it has to its hinterland and to other cities. Taylor and colleagues point out that city‐city relations and city‐hinterland relations can be understood as two sides of a coin. Using this conception the polycentric structure and dynamics of the German urban system can be described through: (i) metropolitan functions representing city‐hinterland relations (cosmopolitanity) and (ii) a network of cities representing city‐city relations (connectivity). Measuring separately the degrees of cosmopolitanity and connectivity, we look at whether the German urban system after reunification has grown together, becoming one balanced urban system, and what role Berlin – as the new capital in the overall system – now has. The results of the two perspectives are compared and analysed.